Antipsychotic drugs and risk of idiopathic venous thromboembolism: a nested case–control study using the CPRD1. (7th September 2014) - Ishiguro, Chieko; Wang, Xi; Li, Lin; Jick, Susan
ABSTRACT Background The evidence to date on the relationship between antipsychotic drugs and the risk of venous thromboembolism (VTE) is limited. Purpose Our aim was to examine the association between the use of typical and atypical antipsychotics and risk of VTE and to assess the effects of dose and duration of use. Methods Among users of typical or atypical antipsychotics between 1998 and 2012 in the Clinical Practice Research Datalink, we identified all VTE cases aged 20–59 years with no major risk factors for VTE. From the same population, we randomly selected up to four controls for each case matched on age, sex, general practice, calendar time, and length of medical history. We estimated adjusted odds ratios (aORs) and 95% confidence intervals (CIs) of VTE for current and recent use of antipsychotics compared with non‐use using conditional logistic regression. Result We identified 868 cases and 3158 matched controls. Compared with non‐use, any current use of antipsychotics was associated with a marginally increased risk of VTE: aOR 1.26 (95%CI [0.97, 1.63]); for new users, the aOR was 3.21 (95%CI [1.64, 6.29]). Prochlorperazine and risperidone were associated with elevated risks of VTE (aORs 2.18, 95%CI [1.47, 3.25], and 1.83, 95%CI [0.88, 3.81], respectively). Conclusion The risk of VTE with typical and atypical antipsychotics varies with type of drug and is highest just after starting the drug. Copyright © 2014 John Wiley & Sons, Ltd.